Morfopragmatika: deminutyvų vartojimas dabartinėje lietuvių kalboje - Savickienė, Ineta (Kalbotyra, 2005)
The use of diminutives often depends on the speech situation: their highest frequency of occurrence is in child-directed speech (COS). Adults use diminutives also when they talk to good friends, and this is especially true for women talking to their girl friends. There are other situations where diminutives in adult-directed speech (ADS) would occur quite often even if people were strangers. That would be used for pragmatic purposes, i.e., in requests, offers, services, etc. It is obvious that the situations just mentioned are not very formal situations; on the contrary, they relate to friendly exchanges. Dressler and Merlini-Barbaresi (1994, 218) define them as ‘not serious’ situations. Therefore, the prevailing meaning of diminutives is closely related to emotions, love and kindness in particular, when the addressee in a speech act is a dear person, especially a child. Unfortunately, there is no source available on the quantitative distribution of diminutives in ADS. Preliminary analysis of the corpus of spontaneous conversations gives the following results: 3,5% (ADS), 53% (CDS), 48% (CS). This supports the common impression that diminutives are used much more often in COS and CS than in ADS.